ANALISIS PEMBERDAYAAN PEREMPUAN PADA NEW VENTURE CREATION: ENTREPRENEURIAL SELF-EFFICACY SEBAGAI VARIABEL PEMODERASI - Kairupan, Daniel Joel Immanuel; Primandaru, Noormalita (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2020)
ABSTRACTThis study focuses on the effects of education empowerement, financial empowerment, and access of technology on new venture creation, with entrepreneurial self-efficacy as a moderating variable, and housewives as the research subject. This study is a cross-sectional field research and uses non-probability purposive sampling method. The research sample is the women in a Family Welfare Movement (Pembinaan Kesejahteraan Keluarga/PKK) group in the coastal village of Bantul. The analysis is conducted by using Partial Least Square (PLS) and based on a structural equation modeling (SEM) in simultaneously testing the measurement model and structural model. Keywords: new venture creation; entrepreneurial self-efficacy; education empowerement; financial empowerment; access of technology ABSTRAKPenelitian ini berfokus pada pengaruh education empowerement, financial empowerment, dan access of technology terhadap new venture creation dan entrepreneurial self-efficacy sebagai variabel pemoderasi pada perempuan ibu rumah tangga. Setting yang digunakan adalah setting alamiah yang juga disebut field research. Dari sisi dimensi waktu, penelitian ini termasuk dalam kategori penelitian cross-sectional. Teknik pengambilan sampel menggunakan non probability sampling tipe purposive sampling. Sampel dalam penelitian ini adalah perempuan yang tergabung dalam kelompok Pembinaan Kesejahteraan Keluarga (PKK) di Desa kawasan pesisir Bantul. Model analisis yang digunakan adalah model analisis Partial Least Square (PLS) mengikuti pola model persamaan struktural (SEM) berbasis varian yang secara stimultan dapat melakukan pengujian model pengukuran sekaligus pengujian model struktural. Kata kunci: new venture creation; entrepreneurial self-efficacy; education empowerement; financial empowerment; access of technology